Pemberdayaan Masyarakat dalam Pengelolaan Sampah Organik Menjadi Pupuk Kompos Menggunakan Compost Bag melalui Program Kampung Zero Waste di RW 06 Menur Pumpungan Surabaya - Shila Radasahila; Sri Andayani; Febby Rahmatullah Masruchin (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
The waste problem not only threatens environmental conditions, but also has serious social and economic impacts in many regions in Indonesia, including the city of Surabaya. This dedication is carried out with the aim of reducing volume and realizing a zero waste paradigm in dealing with global waste problems. The Surabaya City Zero Waste Village Program was realized through outreach to provide awareness for residents to reduce the use of organic and inorganic waste. Apart from that, socialization was also carried out regarding organic waste processing which aims to convert organic waste into compost using Compost Bags, increasing public knowledge about organic waste management and reducing waste from rubbish dumps. This activity includes preparing activity planning, preparation, implementation and evaluation, as well as direct training regarding making compost fertilizer and using Compost Bags. Evaluation is carried out to ensure the success of activities and identify obstacles faced in the process of making compost fertilizer. The Zero Waste Village Program in RW 06 Menur Pumpungan Surabaya in increasing community understanding about managing organic waste into compost using Compost Bags has been successfully implemented with the support of the residents.